Netherlands : School Autonomy and Accountability - World Bank (Washington, DC, 2014)
Education in the Netherlands is highly decentralized. While education policy is the sole responsibility of the Ministry of education, school boards are responsible for delivery. The entire organization of the school system is based on checks and balances to ensure accountability. Budgetary autonomy is established. The school board controls the school budget, with input from parents. Personnel management is established. Salaries are relatively fixed by civil service rules at the primary school level, but completely negotiable at the secondary school level. The school board controls the hiring and firing of teachers and principals. Participation of parents in school governance is established. There is an accountability system comprised of different supervisory institutions where parents are formally represented. School autonomy and accountability are key components to ensure education quality. The transfer of core managerial responsibilities to schools promotes local accountability, helps reflect local priorities, values, and needs, and gives teachers the opportunity to establish a personal commitment to students and their parents. There are five indicators of school autonomy and accountability that can help benchmark an education system's policies that enable school autonomy and accountability: school autonomy in budget planning and approval; school autonomy in personnel management; the participation of the school council in school finance; the assessment of school and student performance; and school accountability to stakeholders. This report focuses specifically on policies in the area of school autonomy and accountability.